In fulfilment of wishes : an exploration of the daydreams of a group of South African adolescent school boys. - Erringtron, Sheri-lee (My University, 2011)
Research on daydreaming and fantasy life has focused predominantly on the fantasies of sexual and violent offenders, often highlighting the daydreaming of youth and its relation to pathology in these populations. Although much is known about the role of these fantasies in relation to the behaviour of criminals, there is little research on the nature and function of sexual and aggressive daydreams in samples of non-clinical populations of adolescent boys. This research, which was informed by psychoanalytic and developmental theories of daydreaming and adolescence, explores the libidinal and aggressive daydreams of a group of South African school boys by investigating: the frequency and conditions of their daydreaming, the characteristic contents of the daydreams, and what understanding they have about the nature and function of daydreaming. 89 boys between 14 and 17 years old, from a private high school in suburban Johannesburg completed a research questionnaire containing 52 closed and open ended questions about their daydreams. The research design included a quantitative frequency analysis of the responses to the closed ended questions, while a form of thematic content analysis was used to interpret the open ended questions. There were four main findings relating to the extent and conditions of daydreaming, the types of wishes present in the content of the daydream descriptions and the participants’ theories of the functions of daydreaming. Firstly, the participants reported to experience predominantly libidinal, as opposed to aggressive daydreams and as frequently as between once and many times every day, drawing attention to theories of the intensification and efflorescence of the sexual drive during adolescence in relation to the nature of daydreaming. Secondly, the extent to which peers, teachers, school and home feature as characters and settings in the participants' daydreams highlighted the role which daily experiences played in influencing the nature and conditions of their reported daydreams. Thirdly, themes of revenge, romance, taboo-breaking and the desire for admiration were the predominant wish-types identified in the participants daydreams, reflecting what appeared to be a ‘normal’ pathway for partially satisfying their needs and a means of reflecting upon the common challenges faced by adolescents. Finally, the adolescent boys themselves most often described daydreaming as wish fulfilling and satisfying desires that cannot be filled in reality, drawing attention to the similarities between their understandings of daydreams and that put forward in psychoanalysis.